Insights on 7p21 deletion including the TWIST1 gene: a case report of an adult patient with macroglossia and a literature review - Alp Peker; Özden Altıok Clark; Mert Coşkun; Ali Duru; Feyza Altunbaş Yalabık; Duygu Gamze Aracı; Aslı Toylu; Sezin Yakut Uzuner; Alper Tunga Derin; Ercan Mıhçı (Egyptian Journal of Medical Human Genetics)
Abstract Background This study presents an adult 7p21 deletion patient, including a literature review specific to 7p21 deletion, and concludes recommendations toward such patients. A 47-year-old male with moderate-to-severe learning disability and significant dysmorphic features was seen in our Medical Genetics clinic. Initially, a chromosome analysis was requested considering a pre-diagnosis of Down syndrome with adult age, and other chromosomal abnormalities. Results In karyotype analysis, one chromosome 7 was observed to have a deletion on its short arm. Subsequently, single nucleotide polymorphism array (SNP Array) analysis was pursued to confirm the abnormality seen in the chromosome analysis and to elucidate its details. The results indicated a 16-megabase loss in the 7p21.3-p15.3 regions. Conclusions Patients with deletions of the short arm of chromosome 7 may exhibit various phenotypic features, including case-specific anomalies. Common abnormalities often linked to the heterozygous loss of 7p21 include a wide nasal bridge and ear shape abnormalities. Our 47-year-old patient presented with macroglossia and dysmorphic traits, suggesting macroglossia as a potential clinical finding for follow-up in adults. Further research is needed to confirm if all such specific anomalies are due to 7p genetic material loss.